Model of Internalizing the Value of Religious Moderation at Universities in Lombok - Hully Hully; Adi Fadli; Mohammad Liwa Irrubai; Irwan Irwan (Yayasan Adra Karima Hubbi, 2024)
Background. The paradigm of religious moderation (wasathiyah Islam) is a style of understanding and practice of Islam or an approach in contextualizing Islamic teachings in the midst of modernization and globalization. Purpose. This study aims to study and find a model for internalizing the value of religious moderation in higher education. Religious moderation is not a new teaching, not a new idiology and also not a new flow, but religious moderation is a way of view, attitude and behavior or religious practice by taking the middle way, acting fairly, balanced and not extreme or not excessive in religion. Method. This research is a qualitative research with data collection using observation, interviews and documentation. Data analysis uses the Miles and Huberman model starting from data collection, data condensation, data display and conclusions/verifying. Data validity was carried out with observation persistence, extension of participation, reference and triangulation. Results. Second, the inculturation model is carried out through exemplary and habituation or habituation in the campus environment. Third, the religious culture model is to create an Islamic campus environment by creating Islamic study centers such as the Qur'an study center and campus da'wah institutions as the basis for the movement to ground moderate Islam in the college environment. Conclusion. In the world of education such as universities, religious moderation becomes a necessity in shaping the character of moderate students.